Endocrine-disrupting compounds in urban rivers of the southern border of Mexico: Occurrence and ecological risk assessment - Khirbet López-Velázquez; José G. Ronderos-Lara; Hugo A. Saldarriaga-Noreña; Mario A. Murillo-Tovar; Minerva Villanueva-Rodríguez; Jorge L. Guzmán-Mar; Edwin R. Hoil-Canul; José L. Cabellos-Quiroz (Emerging Contaminants)
The occurrence of seven endocrine-disrupting compounds (EDCs) in four urban rivers on the southern border of Mexico was studied in this work. The selected EDCs were 17β-estradiol (E2), estriol (E3), 17α-ethinylestradiol (EE2), bisphenol A (BPA), bisphenol F (BPF), 4-nonylphenol (4NP) and 4-tert-octylphenol (4TOP). Water samples from the Coatan, Texcuyuapan, Cahoacan, and Coatancito rivers were collected at three different sites on each river and processed by solid phase extraction (SPE). The samples were analyzed by gas chromatography triple quadrupole tandem mass spectrometry (GC-MS/MS) and compounds of interest were identified by dynamic mass reaction monitoring mode (dMRM). Among the target EDCs, E2, BPA, and 4NP were detected in all water samples, with BPA being the most abundant ranging from 4.22 up to 127.96 ng/L. Correlation tests showed significant positive associations between estrogens and BPA, as well as the correlation between alkylphenols and BPA, suggesting common origin emission sources, which were identified as discharges of untreated municipal wastewater. Finally, the estimation of RQ and EEQ values indicated that the presence of E2, E3, EE2, and BPA in all sampled points represents a high risk for aquatic life in these sites, mainly for Texcuyuapan River, where the aquatic organisms may be susceptible to endocrine disruption by chronic exposure to detected compounds.